Strategi Program Dakwah Majelis Taklim Al-Karim Latifah dalam Memperkuat Ukhuwah Islamiyah di Kota Medan - Nurul Adila Rambe; Hasnun Jauhari Ritonga (Islam & Contemporary Issues, 2026)
This study aims to analyze the da'wah program strategies implemented by the Al-Karim Latifah Islamic Study Group in strengthening ukhuwah Islamiyah among the Muslim community in Medan. This research employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation involving the chairperson of the study group, religious preachers (da'i), committee members, and congregation members as the main informants. The findings indicate that the Al-Karim Latifah Islamic Study Group strengthens ukhuwah Islamiyah through integrated da'wah programs, including regular religious lectures, Qur'an learning activities, social charity programs, and community-based religious events. These programs encourage stronger interpersonal relationships, increase community participation in religious activities, and foster solidarity, mutual assistance, and a stronger sense of belonging among congregation members. The study also finds that the combination of spiritual guidance and social engagement has contributed to sustaining harmonious relationships within the community. The findings imply that community-based da'wah strategies integrating religious education with social empowerment can serve as an effective model for strengthening ukhuwah Islamiyah and promoting social cohesion in urban Muslim communities.